2013
DOI: 10.1007/s11605-013-2215-4
|View full text |Cite
|
Sign up to set email alerts
|

A Simple System to Predict Perihilar Cholangiocarcinoma Resectability

Abstract: XY classification for PHCs suggests that in type Y (free LLC), the tumor is most often resectable, while in type X (LLC involved), the tumor is only resectable using complex vascular reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…A 57-year-old woman with a type 3a PCC invading the main portal vein bifurcation underwent a right hepatectomy with en bloc resection of segment 4b, the caudate lobe, and the extrahepatic common bile duct; hepatic pedicle lymphadenectomy; and main portal vein bifurcation reconstruction. 4 The cross-section of the left biliary plate was tumor-free at frozen section analysis but involved three small biliary ducts originating from segments 2, 3, and 4a. The biliary plate and the distance between each duct were too large to allow unification.…”
mentioning
confidence: 99%
“…A 57-year-old woman with a type 3a PCC invading the main portal vein bifurcation underwent a right hepatectomy with en bloc resection of segment 4b, the caudate lobe, and the extrahepatic common bile duct; hepatic pedicle lymphadenectomy; and main portal vein bifurcation reconstruction. 4 The cross-section of the left biliary plate was tumor-free at frozen section analysis but involved three small biliary ducts originating from segments 2, 3, and 4a. The biliary plate and the distance between each duct were too large to allow unification.…”
mentioning
confidence: 99%
“…OS was also significantly lower in patients with perihilar tumor localization in Bismuth-Corlette III and IV tumors as compared to class I and II tumors probably due to a lower surgical resection rate (20% vs. 50%; p=0.025). Accordingly, Boudjema et al reported higher rates of inoperability associated with vascular invasion in case of infiltration of the confluence of bile ducts [17]. In contrast to these observations OS in dCC was significantly better as compared to intrahepatic or perihilar CC and to the group of patients with GBC.…”
Section: Discussionmentioning
confidence: 95%
“…Since the biliary con uence of the right and left hemi livers is also invaded by the tumor, the right hepatic artery is commonly invaded. Indeed, the biliary con uence is shifted on the right side of the hepatic hilum and at a close vicinity of the right hepatic artery [2]. Type X PHC includes Type IIIb and type IV of the Bismuth-Corlette classi cation.…”
Section: Discussionmentioning
confidence: 99%
“…Chest CT showed no pulmonary extension. This PHC was classi ed as Bismuth IV and type X of Rennes [2]. It was decided to perform left trisectionectomy, caudate lobectomy and resection of the main bile duct with simultaneous resection of the portal vein and right hepatic artery.…”
Section: Case Reportmentioning
confidence: 99%